Lung Ultrasonography in Ruling Out COVID-19 Among Health Care Workers in Two Italian Emergency Departments: A Multicenter Study. (January 2022) - Copetti, Roberto; Amore, Giulia; Giudice, Caterina Anna; Orso, Daniele; Cola, Silvia; Pillinini, Pierpaolo; Rocco, Chiara; Cappello, Dario; Dibenedetto, Alessia Geneve; Meduri, Stefano
Objective: The low sensitivity of the real-time reverse transcription-polymerase chain reaction (rRT-PCR) test on the nasopharyngeal swab for SARS-CoV2 virus could cause infections among health care professionals and could be a source of viral spread. The aim of this study was to verify whether lung ultrasonography (LUS) had a negative predictive value (NPV) high enough to rule out coronavirus disease 2019 (COVID-19) in a cohort of health care employees, working in emergency departments (EDs). Materials and Methods: A multicenter prospective observational study was conducted in two EDs in Northeast Italy. An adjudication committee established the definitive diagnosis of COVID-19. Results: A cohort was enrolled of 155 possible patient cases (two true positives). Twenty-one health care employees presented with suggestive symptoms for COVID-19. The rRT-PCR test was positive in one of the two patients. LUS was suggestive for COVID-19 pneumonia in four patients. The diagnostic accuracy of LUS was 98.7% (95% confidence interval [CI] = 95.4%–99.8%). The NPV was 100% (95% CI = 100%–100%). Conclusion: LUS has a high enough NPV for excluding a COVID-19-related pneumonia in a cohort of health care employees who were exposed to the SARS-CoV2 virus.